Atomic resolution crystal structure of glutaredoxin 1 from Plasmodium falciparum and comparison with other glutaredoxins. (1st January 2014) - Yogavel, Manickam; Tripathi, Timir; Gupta, Ankita; Banday, Mudassir Meraj; Rahlfs, Stefan; Becker, Katja; Belrhali, Hassan; Sharma, Amit
<x xml:space="preserve">Abstract</x> Glutaredoxins (Grxs) are redox proteins that use glutathione (γGlu‐Cys‐Gly; GSH) as a cofactor. Plasmodium falciparum has one classic dithiol (CXXC) glutaredoxin (glutaredoxin 1; PfGrx1) and three monothiol (CXXS) Grx‐like proteins (GLPs), which have five residue insertions prior to the active‐site Cys. Here, the crystal structure of PfGrx1 has been determined by the sulfur single‐wavelength anomalous diffraction (S‐SAD) method utilizing intrinsic protein and solvent S atoms. Several residues were modelled with alternate conformations, and an alternate position was refined for the active‐site Cys29 owing to radiation damage. The GSH‐binding site is occupied by water polygons and buffer molecules. Structural comparison of PfGrx1 with other Grxs and Grx‐like proteins revealed that the GSH‐binding motifs (CXXC/CXXS, TVP, CDD, Lys26 and Gln/Arg63) are structurally conserved. Both the monothiol and dithiol Grxs possess three conserved water molecules; two of these were located in the GSH‐binding site. PfGrx1 has several polar and charged amino‐acid substitutions that provide structurally important additional hydrogen bonds and salt bridges missing in other Grxs.